Citizen participation for heritage intervention. An experience in Lucena (Cordoba) - Navas-Carrillo, Daniel; Mosquera-Adell, Eduardo; Pérez-Cano, María Teresa (My University, 2022)
This paper presents a participatory experience implemented in the medium-sized city of Lucena (Cordoba) to develop a proposal for intervention on fifteen public heritage buildings. The work was based on identifying the network of key actors, including technical and political managers of municipal areas, the Municipal Corporation and society, through representatives of citizens' groups and associations. A dual participatory process has been defined, consisting of interviews with representatives of the different political parties of the Municipal Corporation and a digital survey disseminated among social agents and public servants. The survey has been designed with a common structure of questions for both groups. In addition to statistical information, questions have focused on the cases studies and the collective needs. The internal view, represented by the municipal employees, has been completed with specific questions on the conditions of the workplaces and the functional and logistical needs derived from their job. Individual, collective value and cultural relevance deserve separate mention. The definition of a particular programme of uses and, mainly if it implies changing the existing ones, must necessarily consider the value. At the same time, its relevance on a cultural level makes it possible to detect a general recognition as part of the heritage and identity legacy of the municipality. The importance attached to a building can be a determining factor in accepting substantial changes to it. The survey made it possible to identify response patterns, based on which the research has defined a list of potential uses and the necessary interventions for rehabilitating each of these buildings. In short, the communication aims to demonstrate the usefulness of this type of participatory methodologies also in cultural heritage rehabilitation processes.
Keywords: Patrimonio histórico artístico; Lucena (Córdoba); Architectural Rehabilitation; Enhancement; Heritage and Citizenship; Participatory Processes; Social Recognition